'Using' Crisis of Governance as an Opportunity for 'Re-invention': Why the Supreme Court of India Took To Hearing Public Interest Litigations—A Case Study. (July 2020) - Biswas, Subrata
What do the different State organs do when they face a crisis? Do the suffering institutions successfully re-invent themselves or is it that some other institution uses the crisis to find an 'opportunity' to re-invent itself? Can one's crisis be another's opportunity? This case-study analyses how the Supreme Court of India (hereinafter SCI) reinvented itself in a bid to further the cause of good governance in the country ever since emergency had been clamped on the nation towards the end of 1970s. Surely there has been a crisis of governance in India, caused by the pathetic performance of both the legislature and the executive. It has led to myriad problems in both social and political arenas. If left unaddressed, Indian people might have turned more violent than they already are and that could have perpetrated a failure of democracy in the country. But the SCI has successfully played a positive role in this regard. If the other institutions have failed the people, the Supreme Court has championed their cause. The world's largest democracy stands saved until now. But is it wholly the judges' heartfelt concern for the people that has prompted the Supreme Court to function in this fashion? Did anything go wrong during the emergency? Why is it that it has been more and more active ever since the emergency ended? And why is it that there has been an exponential growth in public interest litigations (hereinafter PILs) in the Supreme Court even though it cannot handle so many cases because of infrastructural paucities? Situating itself in the specific context of PILs entertained by the SCI and supporting it with the theoretical inputs of the so-called 'principal-agent framework', this essay argues that there has been a competition (i.e., between the court and the elected politicians) for 'occupying' more space in the domain of governance since the inception of the Constitution and it is only the Supreme Court that got the right 'opportunity' to achieve its objective in the wake of crisis in governance that became so visible in Indian politics ever since the fag-end of the 1970s. While the court tried other instruments earlier in its game plan vis-a-vis the elected politicians, the crisis situation since the end of the 1970s made it 'invent' a new tool in the form of PILs capable of safeguarding the interests of the people and insulating them against the mindless functioning of multiple state agencies. But how far can the SCI (hereinafter SCI) proceed with this new tool? Is there a risk of 'overusing' it? Does the court not have its own limitations in this regard, too? What should the Supreme Court do in order to avert a fresh 'crisis'?